Status of Child and Woman in Unregistered Marriage: A Study of Family Resilience and Human Security - Pamuji, Widodo Setio (Yayasan Jurnal Perempuan, 2016)
Unregistered marriage is a phenomena that are quite widespread in Indonesia. Functions of family is becoming vulnerable is not registered under the protection of law. This influences the human security especially the status of girls and children in general in Indonesia. This qualitative research investigates the perception and impacts of unregistered marriage in Indonesia. Methods being employed is deep interviews with various stakeholders. Indonesia forbids unregistered marriage since it make the status of children becoming vulnerable.